Analysis of the Learning Process in Body Massage Skills Training for PGOT Beneficiaries at Mardi Utomo Social Service Center (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
PThe Mardi Utomo PGOT Social Service Center (PPS) seeks to empower its beneficiaries (PGOT) through vocational skills training, namely body massage treatments. Body massage treatment training is very easy to do and the level of community demand for massage has been high since ancient times and the capital required is relatively small. This study aims to analyze the process of learning body massage skills for beneficiaries (PGOT) at the Mardi Utomo PGOT Social Service Center (PPS) including the planning, implementation, and evaluation stages. The type of research used is descriptive qualitative. The study was conducted for 5 months followed by 10 female beneficiary respondents aged 20-50 years. Data collection techniques included observation, unstructured interviews with respondents and 2 social workers as supporting informants and document studies. The results of the analysis show that the planning stage of facilities and instructors has been prepared, but the mental readiness, ethics and communication of PGOT beneficiaries are the main challenges. The implementation stage uses direct practice methods. The average score of the initial learning motivation of beneficiaries is 72.8 (moderate category) indicating sufficient enthusiasm. However, motivation decreased in the middle of the learning and increased again at the end. The challenges of adult learning in the evaluation stage show that PGOT beneficiaries are still weak in soft skills such as ethics, interpersonal communication and emotional management. The conclusion of this study is that the implementation of vocational skills training for body massage care at PPS Mardi Utomo faces psychosocial and intrinsic motivational obstacles that have the potential to hinder the achievement of empowerment goals. The success of the program depends on the ability to integrate soft skills (ethics, communication, emotional management) and hard skills (massage techniques) in a balanced manner.